Juvenile Delinquency and Theft: How Law and Criminology Said? - Lasnita, Fiany Alifia; Utama, Muhamad Adji Rahardian (Law Research Review Quarterly, 2020)
The phenomenon of child delinquency is closely related to child crime and according to many experts this is motivated by socially unacceptable behavior such as excessive acts at school, offenses such as running away from home to criminal behavior. Child delinquency is not only criminal acts, but all acts committed by children that are deemed to violate social, school or community values. Children aged 12 to 18 years (Law No. 12 of 2012, is an age range which in a psychological perspective is classified as adolescence which has developmental characteristics that may make it difficult for children to adapt, causing behavioral problems. In many cases of crimes involving children, various theories of criminology and law try to analyze them, starting from the psychological, environmental, and other external factors. This research aims to analyze the crime of theft by coercion (begal) committed by children through an analytical approach to criminological theory and law. This research showed that internal and external factors influence the level of crimes committed by children. In addition, this research has revealed that the Delinquent Subculture and the Differential Association answer why children commit crimes, starting from imitation and environmental factors, including family and school environment.